Adaptive multi-scale convolutional network for plant leaf disease detection and classification - Tejashwini C. Gadag; D. R. Kumar Raja (Institute of Advanced Engineering and Science, 2026)
Plant disease detection is a critical task in modern agriculture, directly impacting crop yield, food security, and sustainable farming practices. Traditional methods rely on expert visual inspection, which is time consuming, inconsistent, and inaccessible in remote areas. This study introduces advanced deep learning (DL) framework, the adaptive multi-scale convolutional network (AMS-ConvNet) optimized for accurate and efficient plant disease identification. Hierarchical feature extraction network (HFEN) integrates the multi-domain attention framework (MDAF) and adaptive scale fusion module (ASFM) to enhance feature extraction and address challenges such as complex natural backgrounds, non-uniform leaf structures, and varying environmental conditions. The proposed framework employs pre trained knowledge adaptation (PTKA) techniques to improve generalization and overcome data scarcity. Comprehensive evaluations on multiple datasets demonstrate the model's better performance, achieving state-of-the-art metrics in precision, recall, F1-score, and accuracy. Furthermore, this approach ensures scalability and adaptability, making it suitable for real field conditions. The study emphasizes the importance of robust, automated solutions in minimizing crop losses, reducing labor costs, and enhancing agricultural sustainability through precision disease management.